Chemoselective synthesis of diaryl disulfides via a visible light-mediated coupling of arenediazonium tetrafluoroborates and CS2 - Leng, Jing; Wang, Shi-Meng; Qin, Hua-Li (Beilstein Journal of Organic Chemistry, 2017)
A highly efficient and chemoselective method for the synthesis of diaryl disulfides is developed via a visible light-promoted coupling of readily accessible arenediazonium tetrafluoroborates and CS2. This practical and convenient protocol provides a direct pathway for the assembly of a series of disulfides in an environmentally friendly manner with good to excellent yields.
Keywords: arenediazonium tetrafluoroborates; carbon disulfide; chemoselectivity; diaryl disulfides; photocatalyst